Plataforma de desenvolvimento de sistemas de controle: estudo de caso aplicado em um agv - Rodrigues, Luan Dias (Universidade Federal de São Carlos, 2026)
Mobile robotics has gained prominence in the industry, especially through the use of AGVs (Automated Guided Vehicles), which contribute to greater efficiency and safety in production processes. To ensure accurate line-following behavior, AGVs rely on controllers, with the PID (Proportional, Integral, and Derivative) being the most commonly used due to its simplicity and effectiveness. This work presents the development of a control systems platform applied to a line-following AGV project. The platform enables the implementation and testing of functionalities, while also ensuring project continuity through a standardized documentation model consisting of seven technical documents and a well-defined software architecture. Practical experiments with the AGV using the PID controller demonstrated proper system operation and validated the platform as an effective tool for preserving project legacy and supporting future enhancements.
Control systems development platform: case study applied to an AGV
Keywords: Controlador PID; Robótica Móvel; UML; Arquitetura de Software; Documentação Técnica; PID Controller; Mobile Robotics; UML; Software Architecture; Technical Documentation; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO; 9. Indústria, Inovação e Infraestrutura